Czy to naprawdę nieważne, jak definiujemy śmierć? - Norkowski, Jacek Maria (Człowiek i Społeczeństwo, 2022)
The Montreal conference (2012) adopted the definition of death as „permanent loss of conscious- ness and permanent loss of all brainstem functions”. This definition aspires to cover with its scope all types of death that could be reduced to this definition as a phenomenon. This definition is based on the assumptions contained in the Harvard Report of 1968, which defined death as an irreversible coma. This approach to death has been criticized by some doctors, philosophers, theologians, lawyers, journalists and religious circles. In most countries, these protests were ignored by state legislation and the influential media, resulting in no apparent social opposition to the neurological criteria for death and the later introduced cardiac death criteria. In some countries, however, the legislation provides for the possibility of objecting to these death criteria, which allows them to be avoided for declaring death by anyone who disagrees with them. Japan and the state of New Jersey in the United States have developed statutory solutions for this purpose that could be an example for other countries. Meanwhile, this is not the case and the societies of most countries in the world have in effect imposed definitions and criteria of death with which 20–40% or even more citizens do not agree. This undermines their civil rights and therefore needs to be changed, especially since there is a desire for further legal changes that would legalize consent to death by organ donation (death by organ donation). This in turn would mean an open questioning of the principle that we do not kill some patients in order to save others, and the mission of doctors is only to heal patients, not to kill them.